Patterns of Physical Activity Outside of School Time Among Japanese Junior High School Students. (23rd July 2013) - He, Li; Ishii, Kaori; Shibata, Ai; Adachi, Minoru; Nonoue, Keiko; Oka, Koichiro
ABSTRACT: BACKGROUND: Physical activity is beneficial for adolescent health. The physical activity patterns of Japanese adolescents are relatively unknown. Therefore, this study aimed to describe the current patterns of physical activity and to identify sex and grade differences among them. METHODS: The participants comprised 714 Japanese adolescents aged 12 to 15 years old (boys N = 372, girls N = 342) from a public junior high school in Okayama, Japan. Physical activity at school, outside of school after hours, and during lunch recess as well as the total leisure time in a usual week was assessed with a 5‐item questionnaire. To assess the differences in the physical activity patterns by sex and grade, independent t tests and analysis of variance (ANOVA) were conducted, respectively. RESULTS: Boys spent significantly more time in physical activity both inside and outside of school settings than girls (p < .05). Higher grade students were significantly less active than lower grade students (p < .05). Furthermore, the physical activity patterns across the grades differed between settings (at school, outside of school during the after‐school period, lunchtime recess, and at home). CONCLUSION: To increase physical activity levels among Japanese adolescents, implementation of after‐school programs or environmental modifications developed within the school setting could be effective strategies.